Regulation of the Warburg Effect in Early-Passage Breast Cancer Cells - Robey, Ian F.; Stephen, Renu M.; Brown, Kathy S.; Baggett, Brenda K.; Gatenby, Robert A.; Gillies, Robert J. (Neoplasia (New York, N.Y.), 2008)
Malignancy in cancer is associated with aerobic glycolysis (Warburg effect) evidenced by increased trapping of [18F]deoxyglucose (FdG) in patients imaged by positron emission tomography (PET). [18F]deoxyglucose uptake correlates with glucose transporter (GLUT-1) expression, which can be regulated by hypoxia-inducible factor 1 alpha (HIF-1α). We have previously reported in established breast lines that HIF-1α levels in the presence of oxygen leads to the Warburg effect. However, glycolysis and GLUT-1 can also be induced independent of HIF-1α by other factors, such as c-Myc and phosphorylated Akt (pAkt). This study investigates HIF-1α, c-Myc, pAkt, and aerobic glycolysis in low-passage breast cancer cells under the assumption that these represent the in vivo condition better than established lines. Similar to in vivo FdG-PET or primary breast cancers, rates of glycolysis were diverse, being higher in cells expressing both c-Myc and HIF-1α and lower in cell lines low or negative in both transcription factors. No correlations were observed between glycolytic rates and pAkt levels. Two of 12 cell lines formed xenografts in mice. Both were positive for HIF-1α and phosphorylated c-Myc, and only one was positive for pAkt. Glycolysis was affected by pharmacological regulation of c-Myc and HIF-1α. These findings suggest that c-Myc and/or HIF-1α activities are both involved in the regulation of glycolysis in breast cancers.